Characteristics and controls of the runout behaviour of non-Boussinesq particle-laden gravity currents – A large-scale experimental investigation of dilute pyroclastic density currents - Brosch E; Lube G; Esposti-Ongaro T; Cerminara M; Breard ECP; Meiburg E (Elsevier B.V., 2022)
One of the most dangerous aspects of explosive volcanism is the occurrence of dilute pyroclastic density currents that move at high velocities of tens to about a hundred of metres per second outwards from volcanic vents. Predicting the runout behaviour of these turbulent flows of hot particles and air is complicated by strong changes in the flow density resulting from entrainment of ambient air, sedimentation of particles, as well as heating and expansion of the gas phase. Current hazard models that are based on the behaviour of aqueous gravity currents cannot capture all aspects of the flow dynamics, and thus pyroclastic density current dynamics remain comparatively poorly understood. Here we interrogate the runout behaviour of dilute pyroclastic density currents in large-scale experiments using hot volcanic material and gas. We demonstrate that the flows transition through four dynamic regimes with distinct density and force characteristics. The first, inertial regime is characterized by strong deceleration under high density differences between the flow and ambient air where suspended particles carry a main proportion of the flows' momentum. When internal gravity waves start to propagate from the flow body into the advancing flow front, the currents transition into a second, inertia-buoyancy regime while flow density continues to decline. In this regime, subsequent arrivals of fast-moving internal gravity waves into the front replenish momentum and lead to sudden short-lived front accelerations. In the third regime, when the density ratio between flow and ambient air decreases closer to a value of unity, buoyancy forces become negligible, but pressure drag forces are large and constitute the main flow retarding force. In this inertia-pressure drag regime, internal gravity waves cease to reach the front. Finally, and with the density ratio decreasing below 1, the current transitions into a buoyantly rising thermal in regime 4. Unlike for aqueous gravity currents, the Froude number is not constant and viscous forces are negligible in these gas-particle gravity currents. We show that, in this situation, existing Boussinesq and non-Boussinesq gravity current models strongly underpredict the front velocity for most of the flow runout for at least half of the flow propagation. These results are not only important for hazard mitigation of pyroclastic density currents but are also relevant for other turbulent gas-particle gravity currents, such as powder snow avalanches and dust storms.